Exploring the quality of end-of-life care in the intensive care unit: a qualitative multiple case study approach with family members of Muslim patients - Robert Fowler; Craig Dale; Ayah Nayfeh; Lesley Gotlib Conn (BMJ Open, 2025)
Objective Muslim patients are an underrepresented community in end-of-life care research, with little evidence around factors that influence the quality and experience of care. The aim of this study was to explore the quality of end-of-life care in the intensive care unit (ICU) from the perspective of next-of-kin family members of Muslim patients.Design A qualitative multiple case study design using semistructured interviews with family members of Muslim patients. Healthcare providers’ notes from the patient medical record were also used to contextualise the patient care experience and medical journey. Data were analysed using deductive content analysis.Setting A large academic tertiary care hospital in Toronto, Canada.Participants Next-of-kin family members of Muslim patients (≥18 years) who were admitted to the ICU and died in hospital between October 2019 and December 2021.Results Family members of five Muslim patients of South Asian descent were recruited for this study. Four central themes were identified: (1) trust and confidence in the healthcare team overseen by medical experts; (2) quality communication with medical experts; (3) achieving patient goals of care; and (4) dignity of care through cultural respect and emotional support. Culture, religion and religiosity did not appear to have a major influence on the medical decision-making process. Communication, emotional and psychological well-being for patients, and cultural respect were identified as possible areas for quality improvement.Conclusions Our findings identified central themes in the quality of end-of-life care for families of seriously ill Muslim patients. These insights can inform clinical processes and interventions to improve the quality of care and reduce psychological and emotional burden at the end of life.